Nanomedicine strategies to target coronavirus (2020)
With the severe acute respiratory syndrome coronavirus (SARS-CoV) in 2002, the middle east respiratory syndrome CoV (MERS-CoV) in 2012 and the recently discovered SARS-CoV-2 in December 2019, the 21st first century has so far faced the outbreak of three major coronaviruses (CoVs). In particular, SARS-CoV-2 spread rapidly over the globe affecting nearly 20.000.000 people up to date. Recent evidences pointing towards mutations within the viral spike proteins of SARS-CoV-2 that are considered the cause for this rapid spread and currently around 200 clinical trials are running to find a treatment for SARS-CoV-2 infections. Nanomedicine, the application of nanocarriers to deliver drugs specifically to a target sites, has been applied for different diseases, such as cancer but also in viral infections. Nanocarriers can be designed to encapsulate vaccines and deliver them towards antigen presenting cells or function as antigen-presenting carriers themselves. Furthermore, drugs can be encapsulated into such carriers to directly target them to infected cells. In particular, virus-mimicking nanoparticles (NPs) such as self-assembled viral proteins, virus-like particles or liposomes, are able to replicate the infection mechanism and can not only be used as delivery system but also to study viral infections and related mechanisms. This review will provide a detailed description of the composition and replication strategy of CoVs, an overview of the therapeutics currently evaluated in clinical trials against SARS-CoV-2 and will discuss the potential of NP-based vaccines, targeted delivery of therapeutics using nanocarriers as well as using NPs to further investigate underlying biological processes in greater detail.